2018
DOI: 10.1039/c7fo01354j
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence, biological activity and metabolism of 6-shogaol

Abstract: As one of the main bioactive compounds of dried ginger, 6-shogaol has been widely used to alleviate many ailments. It is also a major pungent flavor component, and its precursor prior to dehydration is 6-gingerol, which is reported to be responsible for the pungent flavor and biological activity of fresh ginger. Structurally, gingerols including 6-gingerol have a β-hydroxyl ketone moiety and is liable to dehydrate to generate an α,β-unsaturated ketone under heat and/or acidic conditions. The conjugation of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
49
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(58 citation statements)
references
References 144 publications
0
49
0
2
Order By: Relevance
“…Since its structure is thermally unstable, 6-gingerol is converted to 6-shogaol, which has an a,b-unsaturated carbonyl group, as a result of processing techniques such as heating, drying, and steaming (Bhattarai et al, 2001;2007;Dugasani et al, 2010;Kou et al, 2018). Both substances are beneficial to health, but several recent reports have indicated that 6-shogaol is superior to 6-gingerol (Dugasani et al, 2010;Ho and Chang, 2018;Jin et al, 2014;Wang et al, 2017), presumably due to its a,bunsaturated carbonyl group (Kou et al, 2018). An a,bunsaturated carbonyl group is present not only in 6-shogaol, but also in curcumin and chalcone (Rodrigues et al, 2016), which are known to have excellent pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since its structure is thermally unstable, 6-gingerol is converted to 6-shogaol, which has an a,b-unsaturated carbonyl group, as a result of processing techniques such as heating, drying, and steaming (Bhattarai et al, 2001;2007;Dugasani et al, 2010;Kou et al, 2018). Both substances are beneficial to health, but several recent reports have indicated that 6-shogaol is superior to 6-gingerol (Dugasani et al, 2010;Ho and Chang, 2018;Jin et al, 2014;Wang et al, 2017), presumably due to its a,bunsaturated carbonyl group (Kou et al, 2018). An a,bunsaturated carbonyl group is present not only in 6-shogaol, but also in curcumin and chalcone (Rodrigues et al, 2016), which are known to have excellent pharmacological activities.…”
Section: Discussionmentioning
confidence: 99%
“…Steamed ginger ethanolic extract (SGE) is a ginger product in which the 6-shogaol content has been increased through steaming and ethanol extraction. SGE is expected to be more potent than other ginger products due to the a,bunsaturated ketone structure of its side-chain (Kou et al, 2018). In a previous study, SGE was reported to inhibit hepatic lipid accumulation by suppressing the expression of SREBP1c (Srebpf1), a lipogenic transcription factor.…”
Section: Introductionmentioning
confidence: 99%
“…Ginger has been used as an herbal medicine to relieve nausea/vomiting and gastrointestinal discomforts (bloating and pain), but the cellular and molecular mechanisms of its neuronal actions are still unclear . It is known that the pharmacological effect of ginger is mainly produced by its bioactive phytochemicals, including the pungent principle gingerols (including 4‐, 6‐, 8, 10‐, and 12‐gingerols) and their more bioactive dehydrated products, the shogaols (including 6‐, 8‐, and 10‐shogaols) …”
Section: Introductionmentioning
confidence: 99%
“…1,2 It is known that the pharmacological effect of ginger is mainly produced by its bioactive phytochemicals, including the pungent principle gingerols (including 4-, 6-, 8, 10-, and 12-gingerols) and their more bioactive dehydrated products, the shogaols (including 6-, 8-, and 10-shogaols). 3,4 In the last two decades, advances in sensory neurobiology have been made by discovering the transient receptor potential (TRP) channel family that are responsible for mediating noxious sensations induced by commonly used pungencies. Among them, TRPV1 is activated by capsaicin in hot peppers, TRPA1 can be activated by isothiocyanate in horseradish, cinnamaldehyde in cinnamon, and thiosulfinates in garlic, and TRPM8 is responsible for the "cooling" sensation of menthol in peppermint.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, shogaols have been suggested to be more effective than gingerols in attenuating the patients' uncomfortable and status. And, 6-shogaol is the most dominant one [30]. However, the molecular mechanism and metabolic fate of shogaols, including 6-shogaol, in antagonizing and improving the status of these diseases have not been clearly identified.…”
mentioning
confidence: 99%